TiB2‐Modified Polymer‐Derived Ceramic SiCN Double‐Layer Thin Films Fabricated by Direct Writing for High‐Temperature Application. Issue 10 (5th May 2022) - Wu, Chao; Lin, Fan; Pan, Xiaochuan; Cui, Zaifu; He, Yingping; Chen, Guochun; Liu, Xianlong; He, Gonghan; Chen, Qinnan; Sun, Daoheng; Hai, Zhenyin
Abstract : The thermal stability at high temperatures is the first design principle of high‐temperature thin‐film sensors. To improve the thermal stability of the thin‐film sensor, a TiB2 ‐modified SiCN double‐layer thin‐film resistor grid with a thickness of 18 μm is fabricated on an alumina substrate via direct writing. Owing to their in situ–generated SiO2 –B2 O3 –TiO2 thermally grown oxide protective layer on the surface and TiB2 percolation paths inside, the produced films exhibit large high‐temperature oxidation resistance, electrical conductivity and high‐temperature‐resistance stability. In the thermal cycling test up to 800 °C, the TiB2 ‐modified SiCN films exhibit a negative‐temperature coefficient of resistance and excellent repeatability and stability. The resistance change rate at 800 °C for 1 h is only 1.1%. With the flexible manufacturing and high‐temperature stability of such ceramic films, this work on double‐layer ceramic films can be applied to in situ monitoring of hot components at high temperature. Abstract : The thermal stability at high temperatures is the first design principle of high‐temperature thin‐film sensors. Herein, a TiB2 ‐modified SiCN double‐layer high‐temperature antioxidation ceramic film is fabricated by direct writing. Due to the in situ–generated SiO2 –B2 O3 –TiO2 thermally grown oxide protective layer on its surface and TiB2 percolation path inside, its operating temperature is up to 800 °C.